PENGARUH PERENCANAAN PASIEN PULANG (DISCHARGE PLANNING) YANG DILAKUKAN OLEH PERAWAT TERHADAP KESIAPAN PASIEN TB PARU MENGHADAPI PEMULANGAN - Dewi ' Ernita; Siti ' Rahmalia; Riri Novayelinda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this study was to identify the influence discharge planning study performed by nurses among pulmonary TB patient's The method is quasi-experimental design, the equivalent control group design approach. The research was conducted in Medical General Hospital Arifin Achmad Pekanbaru involving 15 respondents. The sampling method is purposive sample. The data was colled by using a guestommaire who have been make by health departement systematic republic Indonesia. The analysis used univariate and bivariate is the dependent t test. The result showed that there is very significantly the effect of discharge planning for readiness home care among pulmonary TB Patients (p value= 0,000). The results of this study recommend the discharge planning can provide a regularly and proper conduct discharge of patients with pulmonary TB to avoid the drop out when the drop out drugs and hospital again in RSUD Arifin Achmad Pekanbaru. Keywords: discharge planning, preparedness, pulmonary TB Bibliography: 42 (2004-2013)